1994
DOI: 10.1017/s0022149x00013602
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmicity of egg production by Heligmosomoides polygyrus in wild wood mice, Apodemus sylvaticus

Abstract: The rhythmicity of egg production by Heligmosomoides polygyrus (Nematoda) in wild caught wood mice (Apodemus sylvaticus) was studied. Faecal production followed a 24 h cycle, with peaks at 0400 h and troughs at 1300–1900 h. The patterns in eggs per gram of faeces (EPG) and total eggs were similar to each other, though the former was more accentuated. Both of these followed a 24 h cycle, with peaks coinciding with troughs in faecal production and vice versa. Faecal weight was inversely correlated with EPG, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Several studies have shown that parasitic nematodes display biological activity rhythms that are adjusted to the circadian rhythm of their host or carrier/vector (32)(33). GPCRs like the PDF receptors, which are involved in control of locomotion, make interesting targets for the development of novel, more selective and environmentally friendly antihelminthic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that parasitic nematodes display biological activity rhythms that are adjusted to the circadian rhythm of their host or carrier/vector (32)(33). GPCRs like the PDF receptors, which are involved in control of locomotion, make interesting targets for the development of novel, more selective and environmentally friendly antihelminthic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (1994a) studied the epizootiology of H. polygyrus in a population of A. sylvaticus in England and proved an overdispersed distribution of the nematode, with higher prevalence of infestation in males and heavier rodents. The prevalence of infestation was highest in spring and declined in autumn, and infected rodents moved more often and faster than uninfected rodents (Brown et al 1994b). The reasons for these results are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1989) and as the prepatency period of H. polygyrus from egg to egg was 13–15 days long (Keymer 1985), each individual was treated once a month. Heligmosomoides polygyrus egg production follows a 24‐h cycle fluctuation (Brown et al. 1994b) and to avoid a possible temporal effect in faeces collection we randomized the order of collection of faeces samples between the trapping grids and the grids themselves.…”
Section: Parasite Manipulationmentioning
confidence: 99%